Structural Equation Model of The Success of Exporting the Fresh Durian Business of Thailand to China Under the Creative Economy Strategy and Competitive Advantage - Phiphopaekasit, Phairhoote; Piphop, Buppha; Wacharapibulwong, Thanatmet (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This article aimed to (1) study the level of success in exporting the fresh durian business of Thailand to China under the creative economy strategy and competitive advantage and (2) develop and validate the structural equation model of the success of exporting the fresh durian business of Thailand to China under the creative economy strategy and competitive advantage. The sample group was fresh durian export entrepreneurs, 320 people, and the instrument for collecting data used in this research was a questionnaire. The data were analyzed using mean, percentage, standard deviation, and structural equation model analysis. The research results were as follows: (1) The levels of success of exporting the fresh durian business of Thailand to China under the creative economy strategy and competitive advantage in overall were at the highest level, and (2) the structural equation model of the success of exporting the fresh durian business of Thailand to China under the creative economy strategy and competitive advantage was consistent with the empirical data: Chi-square (χ²) = 73.931, P-value = .480, GFI = .973, AGFI = .951, CFI = 1.000, and RMSEA = 0.000. The influence of factors affecting the success of exporting the fresh durian business of Thailand to China under the creative economy strategy and competitive advantage found that the competitive advantage (CA) has the most positive direct influence on the success in exporting fresh durian businesses (SB), equal to .467. The findings of this research indicated that competitive advantage had the strongest positive direct influence on success in exporting fresh durian businesses. Therefore, the fresh durian export entrepreneurs in Thailand should continuously develop their competitive advantage.